Pengaruh campuran bahan bakar pertalite-bioetanol biji sorghum pada mesin bensin - Abdi Hanra Sebayang; Husin Ibrahim; Surya Dharma; Arridina Susan Silitonga; Berta Br Ginting; Natalina Damanik (Universitas Gadjah Mada, 2020)
The depletion of fossil fuels, rising of earth temperatures and declining of air quality are an unavoidable phenomenon today. This condition is a result of increased and excessive use of fossil fuels. Bioethanol fuel is one solution to reduce this problem that is sourced from renewable raw materials. Sorghum seeds are raw materials that have the potential to be made bioethanol due to they have a high carbohydrate content (70%). The test is performed the use of pertalite-bioethanol blends fuels was on a four-stroke gasoline engine without modification. The percentage of the mixture volume of fuel used is 10% bioethanol-90% pertalite (E10), 15% bioethanol-85% pertalite (E15) and 20% bioethanol-80% pertalite (E20). Engine speeds vary from 1000 to 4000 rpm, and properties of the sorghum seeds bioethanol-pertalite blends are measured and analyzed. The purpose of this study is to investigate engine performance and exhaust emissions at gasoline engine by using the sorghum seeds bioethanol-pertalite blends with different mixed ratios (E10, E15 and E20). The Engine performance includes engine torque, brake specific fuel consumption (BSFC) and thermal brake efficiency (BTE) analyzed. In addition, carbon monoxide (CO), hydrocarbon (HC), and nitrogen oxide (NOx) emissions are measured as gasoline engine exhaust emissions. The results show that BSFC decreased while BTE increased for a fuel blends containing 20% bioethanol at 3500 rpm engine speed, with each maximum value of 246.93 g/kWh and 36.28%. It is also found that CO and HC emissions are lower for the sorghum seeds bioethanol-pertalite blends. Based on the research results, it can be concluded that the sorghum seeds bioethanol-pertalite blends can improve engine performance and reduce exhaust gas emissions.